OP20 A Comparative Analysis of Deployment Associated Mental Health Issues in United States and United Kingdom Armed Forces. (17th September 2012) - Sundin, J; Fear, NT; Greenberg, N; Riviere, L; Herrell, R; Adler, A; Hoge, C; Bliese, P; Wessely, S
Abstract : Background: There are several differences in health outcomes between UK and US military personnel who have deployed to the recent conflicts in Iraq or Afghanistan. Rates of survey-based posttraumatic stress disorder (PTSD) tend to be higher in US personnel, whilst self-reported rates of alcohol use tend to be higher in UK personnel. To explore potential reasons why mental health prevalence rates differ in the two countries a comparative analysis of UK and US Armed Forces combined data was carried out. Methods: Two samples of UK (n=313) and US (n=1560) regular enlisted Army male personnel who were deployed to Iraq in 2007 were combined. Primary outcomes included PTSD, alcohol use, anger and physical symptoms. The samples were compared on a list of 11 combat experiences, socio-demographics and military characteristics. Results: There were several differences between the UK and US samples: the UK sample was younger, more likely to hold a degree and a rank of officer, had served for a longer time, more likely to be married or in a long term relationship, and more likely to rate their marriage as good. The US sample reported more combat experiences. The samples did not differ on physical symptoms, but the US sample was more likely to report PTSD, adjusted odds ratio (AOR) 1.75 (95% Confidence Interval 1.01 – 3.03) and less likely to report alcohol misuse, AOR 0.27 (95% CI 0.20 –0.37) compared to the UK sample. Conclusion: US military personnel deployed to Iraq were more likely to report PTSD whilst UK personnel are more likely to report alcohol misuse. Whilst, there were several differences between the US and UK samples in terms of socio-demographics and combat experiences, these did not explain the difference in health outcomes. Understanding the differences, as well as the similarities, between the UK and US Armed Forces is important, as it can influence the way military personnel are managed in both nations. It can also influence the way military personnel who have developed mental health problems as a result of their service are treated.